KRT6A, KRT6B, PKP1, and PKP3 as key hub genes in esophageal cancer: A combined bioinformatics and experimental study - Shayan Marhamati; Morvarid Hamrahjoo; Zeinab Seyedkhan; Mahdi Bahmani; Nasrin Ziamajidi; Iraj Khodadadi; Mohadese Pouryani; Roghayeh Abbasalipourkabir (Biochemistry and Biophysics Reports)
Esophageal cancer (EC) is the eighth most common cancer in the world. Due to poor survival rates and severe side effects of current therapies, there is a need for a better understanding of the mechanisms and signaling pathways involved in EC. In this study, we downloaded the microarray datasets GSE157808 and GSE92396 from the Gene Expression Omnibus (GEO). Differentially expressed genes (DEGs) were identified using R software and validated through the GEPIA and TIMER databases. CytoHubba was used to extract hub genes from the overlapping DEGs. The TIMER database was employed to assess correlations between gene expression and immune infiltration. Additionally, hub gene expression was analyzed in 20 pairs of EC tissue samples through RT-qPCR and Western blot. We evaluated clinicopathological correlations and diagnostic potential. We identified 83 overlapping DEGs across the datasets. Subsequently, based on the highest number of degrees in the hub gene network, the KRT6A, KRT6B, PKP1, and PKP3 genes were selected for further experimental analysis. EC samples showed upregulated expression of these genes, consistent with our bioinformatic analysis and the GEPIA and TIMER databases. However, KRT6B protein levels were not significantly elevated. KRT6A expression was associated with lymph node metastasis, while KRT6B showed an inverse relationship with necrosis. Gene expression levels correlated with components of immune infiltration. ROC analysis indicated possible diagnostic value, while Kaplan-Meier plots showed no significant association with survival outcomes. Elevated expression of KRT6A, KRT6B, PKP1, and PKP3 is associated with EC, indicating their potential as candidates for further investigation.